2019
DOI: 10.3389/fphar.2019.00362
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Inhibits Human Endothelial Cell Proliferation and Tube Formation

Abstract: Recent clinical trials revealed that sodium-glucose co-transporter 2 (SGLT2) inhibitors significantly reduce cardiovascular events in type 2 diabetic patients, however, canagliflozin increased limb amputations, an effect not seen with other SGLT2 inhibitors. Since endothelial cell (EC) dysfunction promotes diabetes-associated vascular disease and limb ischemia, we hypothesized that canagliflozin, but not other SGLT2 inhibitors, impairs EC proliferation, migration, and angiogenesis. Treatment of human umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…Meanwhile, the angiogenic factors secreted by dapagliflozin-treated skeletal muscle cells could stimulate both vascular endothelial and smooth muscle cells’ proliferation and migration potentials. These results are consistent with those of previous studies, showing that 10 μM dapagliflozin did not affect the proliferation and migration of vascular endothelial cells ( Mancini et al., 2018 ; Behnammanesh et al., 2019 ), as well as those of smooth muscle cells ( Behnammanesh et al., 2020 ). Together, these results suggest that intramuscularly-administered dapagliflozin exerts its function in inducing neovascularization and blood perfusion recovery by promoting the paracrine function of skeletal muscle cells, which in turn enhances the proliferation and migration potentials of vascular endothelial and smooth muscle cells.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, the angiogenic factors secreted by dapagliflozin-treated skeletal muscle cells could stimulate both vascular endothelial and smooth muscle cells’ proliferation and migration potentials. These results are consistent with those of previous studies, showing that 10 μM dapagliflozin did not affect the proliferation and migration of vascular endothelial cells ( Mancini et al., 2018 ; Behnammanesh et al., 2019 ), as well as those of smooth muscle cells ( Behnammanesh et al., 2020 ). Together, these results suggest that intramuscularly-administered dapagliflozin exerts its function in inducing neovascularization and blood perfusion recovery by promoting the paracrine function of skeletal muscle cells, which in turn enhances the proliferation and migration potentials of vascular endothelial and smooth muscle cells.…”
Section: Discussionsupporting
confidence: 93%
“…It was speculated that tumor-PLT crosstalk can enhance the tube formation ability of HUVECs. Tube-forming experiments are a rapid and quantifiable method to measure angiogenesis in vitro ( 41 ). The present study investigated the effect of H1975-PLT crosstalk on HUVEC angiogenesis using junction number, mesh number and total length as indicators of tube-forming ability, and the results of the present study confirmed that the tube-forming ability of HUVECs could be promoted by H1975-PLT crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Another SGLT2 inhibitor, canagliflozin has proven to be an inhibitor of endothelial cells (ECs) proliferation and DNA synthesis [ 84 ]. The process of controlling EC growth has been shown to play a pivotal role in atherogenesis inhibition [ 85 ].…”
Section: Anti-inflammatory Properties Of Sglt2i May Slow Down Athementioning
confidence: 99%